PROSES PENYIDIKAN TINDAK PIDANA PENIPUAN PENERIMAAN PEGAWAI NEGERI SIPIL DI KEPOLISIAN RESOR MOJOKERTO KOTA - Susanto, Wahyu; Cornelis, Vieta Imelda; Handayati, Nur (COMMUNITY OF RESEARCH LABORATORY (KELOMPOK KOMUNITAS LABORATORIUM PENELITIAN), 2024)
This study aims to analyze the process of investigating the criminal act of fraud in the acceptance of civil servants and the factors that cause the criminal act in the Mojokerto City Resort Police. The research method used is empirical juridical with a qualitative approach. The results showed that the investigation process had run according to the procedure. The factors causing this criminal offense consist of internal factors such as the civil servant recruitment system, laws and regulations, and law enforcement, as well as external factors such as forced conditions, the existence of opportunities to commit crimes, pressure from certain parties, and the nature of a person. It is recommended that the Mojokerto City Resort Police increase human resources and conduct socialization to the community to prevent this crime. The public is also expected to be more confident in participating in the CPNS selection process honestly and realize that paying state apparatus in the selection process is a crime.